2013
DOI: 10.1124/jpet.113.208959
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment of Efflux Transport in Sunitinib Distribution to the Brain

Abstract: This study quantitatively assessed transport mechanisms that limit the brain distribution of sunitinib and investigated adjuvant strategies to improve its brain delivery for the treatment of glioblastoma multiforme (GBM). Sunitinib has not shown significant activity in GBM clinical trials, despite positive results seen in preclinical xenograft studies. We performed in vivo studies in transgenic Friend leukemia virus strain B mice: wild-type, Mdr1a/b(2/2), Bcrp1(2/2), and Mdr1a/b(2/2)Bcrp1(2/2) genotypes were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
2
53
1
Order By: Relevance
“…However, in the presence of both the P-gp and Bcrp inhibitors, the raltegravir P eff increased significantly in both the jejunum and ileum segments, suggesting a cooperative activity of these transporters in restricting raltegravir intestinal permeability. The cooperative function of P-gp and Bcrp transporters in the brain accumulation of the anticancer drug sunitinib was reported previously (45). In addition, previous studies have reported that raltegravir accumulation and permeability in Caco-2 cells are dependent on intestinal lumen pH (41,46), suggesting that the oral absorption of raltegravir might be altered by changes in luminal pH, as well as the expression and/or activity of the drug efflux transporters at the blood-intestinal barrier.…”
Section: Figsupporting
confidence: 61%
“…However, in the presence of both the P-gp and Bcrp inhibitors, the raltegravir P eff increased significantly in both the jejunum and ileum segments, suggesting a cooperative activity of these transporters in restricting raltegravir intestinal permeability. The cooperative function of P-gp and Bcrp transporters in the brain accumulation of the anticancer drug sunitinib was reported previously (45). In addition, previous studies have reported that raltegravir accumulation and permeability in Caco-2 cells are dependent on intestinal lumen pH (41,46), suggesting that the oral absorption of raltegravir might be altered by changes in luminal pH, as well as the expression and/or activity of the drug efflux transporters at the blood-intestinal barrier.…”
Section: Figsupporting
confidence: 61%
“…Rajneet et al found that overall, these findings indicate that there is a cooperation at the blood-brain barrier (BBB) in restricting the brain penetration of Sunitinib, and brain delivery can be enhanced by administration of a dual inhibitor of P-gp and Bcrp [40]. Therefore, our study provides a novel insight in improving Suntinib efficacy with genetic manipulation.…”
Section: Mir-145 Enhanced Cytotoxic Effect Of Sunitinib By Inhibitingsupporting
confidence: 55%
“…Many drugs are substrates for more than one efflux transporter, and several murine studies have shown that for these poly-transporter substrates, selective chemical inhibition or genetic knock-out of only one transporter has minimal effect on brain accumulation, but simultaneous inhibition or genetic knock-out of all members of the relevant transporter suite markedly increases brain biodistribution. [36][37][38] Thus, because BBB efflux transporters work in concert, unless cyclosporine were to inhibit all BBB transporters responsible for methadone efflux (assuming methadone is actually an efflux transporter substrate in vivo), inhibiting less than the full efflux transporter suite might not alter methadone pharmacodynamics. Therefore, the present results do not exclude the possibility that methadone is a substrate for one or more (non-cyclosporine inhibitable) efflux transporters at the human BBB.…”
Section: Discussionmentioning
confidence: 99%